Earthworm communities under an agricultural intensification gradient in Colombia - Decaëns, Thibaud; Jiménez Jaén, J.J. (Springer, 2002)
This study was carried out in the Eastern Plains of Colombia and assessed the impact of agricultural intensification on the structure of earthworm communities. Earthworms were hand-sorted in a variety of agroecosystems of increasing intensity, from natural savanna to pastures and annual crops. An agricultural intensification index was used to rank systems along an intensification gradient, i.e. from native savanna to pastures and annual crops. Earthworm biomass, specific richness and Shannon index sharply decreased along the gradient. The disappearance of some species in cultivated systems was mostly attributed to the lack of recovery of populations after major perturbations like e.g. tillage. The more resistant species were those presenting high surface mobility (i.e. high colonisation capacity) or high population growth potential (i.e. high ability of population recovering after perturbation). Sensitive species disappeared after pasture establishment but richness was recovered in a period of about 3 years. In 17 year-old pastures, the community has regained its initial diversity and present very high biomass due to the presence of abundant populations of an anecic species. On the opposite side, annual crops had deep detrimental impacts that were more accentuated in the rotations (i.e. systems that were tilled twice a year) and were still present in a 2 year-old fallow.